Semi-automated three-dimensional reconstruction of cervical paravertebral muscles based on CT images to explore the relationship between cervical flexors and extensors and cervical lordosis - Yuelin Cheng; Xinyan Zhao; Zehua Jiang; Mengmeng Zhou; Hao Yu; Linyan Liu; Xuanhao Fu; Rusen Zhu (BMC Musculoskeletal Disorders)
Abstract Background Cervical spondylotic myelopathy (CSM) is closely related to paraspinal muscles (PSM). Cervical lordosis, as a crucial parameter for assessing the sagittal balance of the cervical spine, its alteration can have a substantial impact on the progression of CSM. In this research, semi - automatic three - dimensional reconstruction of PSM in CSM patients was carried out via CT, and the changing patterns of PSM and its relationship with cervical lordosis were explored. Methods The subjects of this study were patients diagnosed with CSM at our hospital between 2022 and 2023. Semi-automated three-dimensional reconstruction of the PSM of the patient's cervical spine was performed by 3Dslicer software, and the patient's muscle volume (MV), effective muscle volume (EMV) and fat infiltration rate (FIR) were calculated. Additionally, we measured the lateral Cobb angle of the cervical spine. Patients were categorized into two groups based on the lateral Cobb angle: Cobb > 0° and Cobb < 0°. We subsequently analyzed the relationship between the patients' flexor and extensor muscles and cervical lordosis. Results Fifty-five patients were included in the study. Significant differences were observed in the MVRD (Muscle volume ratio of deep cervical flexors and extensors), EMVRD (Effective muscle volume ratio of deep cervical flexors and extensors), MVR (Muscle volume ratio of cervical flexors and extensors), and EMVR (Effective muscle volume ratio of cervical flexors and extensors) of the cervical vertebrae C3-6 between the two groups. The MVRD, EMVRD, MVR, and EMVR of the patient's cervical vertebrae C3-6 exhibited negative correlations with both the lateral and flexion Cobb angles. In contrast, the extension Cobb angle was negatively correlated only with the MVRD and EMVRD of the cervical vertebrae C3-6. Conclusions A significant difference in the ratio of cervical flexors and extensors between the two groups of patients, which is negatively correlated with the lateral Cobb angle. The ratio of flexor and extensor muscles at the C4 segment may change most significantly compared with other segments. Furthermore, the ratio of flexor to extensor muscles is associated with the Cobb angle during both flexion and extension.